(untitled) (Revista de Ciências Agroveterinárias, 2008)
Wine is an alcoholic beverage of complex composition due to the biological, chemical, physical and enzymatic transformations that occur during its processing. Among natural factors, climatic conditions on grape maturation can influence the concentration of sugar and organic acids and the content of volatile and fenolic compounds. This work had as objective to compare wine quality during the vinification, from the Cabernet Sauvignon cultivar, harvested at two different production regions of Santa Catarina (Lages and São Joaquim), through physical-chemical monitoring of the compounds and sensorial evaluation. Wine was elaborated through microvinification, in the 2006 growing season. Samples for determining physical and chemical characteristics of winemaking were collected as follows: analyze of the most, immediately after grape crushing, and analyze of the wine, on maturation. Results indicated that wine from São Joaquim showed superior grades of alcohol, total acidity, total poliphenols, anthocyanins and tannins than that from Lages. The wine from São Joaquim also presented larger color intensity, greater acidity and astringency and more body, in the sensorial evaluation.